1975
DOI: 10.1111/j.1600-0773.1975.tb00812.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cyclophosphamide and Azathioprine on Collagen in Skin and Granulation Tissue in Rats, and the Effects of Cyclophosphamide on Collagen in Human Skin

Abstract: Granulation tissue was produced in rats by subcutaneous implantation of cellulose sponges. The effect of daily intraperitoneal injections of cyclophosphamide or azathioprine on rat skin and granulation tissue was examined after 14 and 42 days. Skin biopsies from patients with glomerulonephritis were analyzed before and after 42 days of treatment with cyclophosphamide or placebo. In the rats, cytostatic treatment caused an increase in the dry weight of the skin, and azathioprine increased the dry weight and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…An approximately 5% decrease in the haemoglobin concentration of the blood and a 50% decrease in the leucocyte count were noted after cyclophosphamide treatment as previously reported (Hansen & Lorenzen 1975a). An approximately 5% decrease in the haemoglobin concentration of the blood and a 50% decrease in the leucocyte count were noted after cyclophosphamide treatment as previously reported (Hansen & Lorenzen 1975a).…”
Section: Effect Of Cyclophosphamidesupporting
confidence: 81%
See 1 more Smart Citation
“…An approximately 5% decrease in the haemoglobin concentration of the blood and a 50% decrease in the leucocyte count were noted after cyclophosphamide treatment as previously reported (Hansen & Lorenzen 1975a). An approximately 5% decrease in the haemoglobin concentration of the blood and a 50% decrease in the leucocyte count were noted after cyclophosphamide treatment as previously reported (Hansen & Lorenzen 1975a).…”
Section: Effect Of Cyclophosphamidesupporting
confidence: 81%
“…In previous studies on the effect of cyclophosphamide on collagen in rat skin and granulation tissue, it was observed that cyclophosphamide inhibits the biosynthesis as well as the degradation of collagen and possibly also inhibits the crosslinking of collagen and the hydroxylation of proline (Hansen & Lorenzen 1975a& b, 1977. These effects may be of importance in the action of cyclophosphamide in patients with inflammatory connective tissue diseases, such as rheumatoid arthritis.…”
mentioning
confidence: 99%
“…tion in the treatment of immunological and inflammatory diseases in addition t o being a frequently used antineoplastic agent (Stevens & Willoughby 1969;Currey 1971;Hill 1975). T h e effects o n connective tissue have, therefore, attained increasing interest in experimental work with this compound (Bagley et al 1973, Hansen & Lorenzen 1975.…”
mentioning
confidence: 99%
“…Effects by the drug on the hydroxylation of proline have been suggested by Hansen & Lorenzen (1975), but are not likely to be of any significance in the present context as stable, extracellular collagen is not formed without at least 90% hydroxylation (Prockop et a/. 1979).…”
Section: Discussionmentioning
confidence: 83%
“…The main target of activated cyclophosphamide is supposed to be the guanine bases of the DNA molecule, leading to cross-link formation between the double helices and impaired replication (Brock & Hohorst 1963& 1967. Some reports, however, suggest that alkylating agents may change the activities of enzymes involved in amino acid metabolism (Hill 1975) or exercise a direct influence o n structural proteins (Dorner & Uddin 1968;Hansen & Lorenzen 1975).…”
mentioning
confidence: 99%